Perlindungan Hukum Hak Cipta di Media Sosial: Studi Kasus Pinterest - Muhammad Farhan; Grasia Kurniati; Devi Siti Hamzah Marpaung (Universitas Widya Gama Malang, 2022)
Legal protection in this very modern era needs further attention, especially to technology that is always developing rapidly. The current era of social media is very diverse, one of which is the social media Pinterest, where social media facilitates various photos contained in it. The media in the form of images must be able to give legal protection to the creators of the works who have exclusive rights in the form of privileges so that they are not misused by others for their commercial interests. The purpose of this study is to find out the legal protection of Pinterest social media and as legal reading material for Pinterest social media users with normative juridical methods for the research method. The result of this study is that the image media contained in Pinterest is copyright protected under Article 40 Paragraph (l) letters f and k of Law Number 28 of 2014 concerning Copyright, where there are sanctions given to copyright violators, namely sanctions in the form of fines at most a lot of 4 billion rupiah.